Identificación y análisis de métodos heurísticos basados en reglas de prioridad para la solución de problemas de programación de múltiples proyectos con recursos restringidos (RCMPSP) (2017)
The solution to the RCPSP problem has been extensively studied since the 1950s, accurate, heuristic and metaheuristic methods have been developed to solve the problem of optimal allocation of resources and to obtain sequences of activities That minimize performance measures such as completion time and project delays, however, most of the companies that develop projects are operating in a multiproject environment and must lead to the problem of allocation of resources that are shared among projects to maximize The objectives of their project portfolios. This work deals with the problem of multiproject programming with restricted resources by identifying and analyzing heuristic methods based on priority rules to minimize the most commonly used performance measures in the literature. We study 18 priority rules on a set of 14 instances taken from the literature to minimize 10 performance measures used to measure the performance of each priority rule and to obtain a better to worse ordering rule with respect to each performance measure. The use of resources (AUF) and the complexity of the network (C) in improving the completion time of the multiproject are also studied in this document.